Julia Stoschek Collection : Fire in my Belly. - Stoschek, Julia; Long, Lisa; Julia Stoschek Foundation (Berlin : Julia Stoschek Foundation, 2021)
Al-Maria, Sophia ; Ahwesh, Peggy ; Bonvicini, Monica ; Bernadette Corporation ; Chan, Paul ; Demand, Paul ; Dewes, Maria Anna ; Diefenbach, Karl Wilhelm ; Donnelly, Trisha ; Dzama; Marcel ; Emin, Tracey ; Enright, Brock ; Gaillard, Cyprien ; Hammer, Barbara ; Hekmat, Leila ; Imhof, Anne ; Jafa, Arthur ; Johnson, Rindon ; Leonard, Zoe ; Lidén, Klara ; McEwen, Adam ; Medieta, Ana ; Madizabal, Asier ; Montgomery, Colin ; Mntambo, Nandipha ; Piper, Adrian ; Prouvost, Laure ; Pruitt, Rob ; Rhode, Robin ; Rogers, Bunny ; Simnett, Marianna ; Smith, Jack ; P. Staff ; caner teker, Williams, Kandis ; Wojarnowicz, David
A FIRE IN MY BELLY, JSC Berlin, 2021
boek